Transesterification of palm oil into biodiesel using ChOH ionic liquid in a microwave heated continuous flow reactor - Sanphawat Phromphithak (2020)
© 2020 Elsevier Ltd Palm oil is one of the most rapidly expanding equatorial crops, which is suitable for feedstock of biodiesel production. In this work, production of methyl esters from palm oil transesterification in a microwave heated continuous flow system was investigated. Choline hydroxide (ChOH) was employed as a green ionic liquid catalyst. The oil to methanol molar ratio, flow rate, power of the microwave, and catalyst loading were varied and optimized by response surface methodology combined with the Box-Behnken design of experiments for maximum biodiesel yield. The ionic liquid proved to be effective in tranesterification of palm oil. The quadratic regression model can be used to forecast the resulting methyl esters content. The optimum condition was identified at molar ratio between oil to methanol of 1:13.2, flow rate of 20 ml/min, microwave power of 800 W and catalyst loading of 6% (w/w), giving the methyl esters content almost 90% in EN 14103 standard test. In addition, most properties of the biodiesel considered were observed to meet the fuel specifications from the ASTM D6751 and Thai standards (community use). Reusability of the ionic liquid for several times was demonstrated before it was contaminated and decomposed, leading to a marked drop in catalytic activity.